Development of industrial relations in India - Kumar, C B; Anstey,Vera (fwd.) (Bombay, 1961)
The term 'industrial relations' is sometimes used to cover the whole field of relationship that grows out of employ ment. Thus Dale Yoder, in his well-known work Personnel Management and Industrial Relations, includes recruitment, selection and training of workers, personnel management as well as collective bargaining policies and practices in the term industrial relations. In the present book, the scope of the subject is more restricted and covers mainly the collec tive relations between the employers' and workers' bodies. This use of the term is in accordance with the practice fol lowed by the International Labour Offic and a number of writers on the subject of industrial relations. Under the heading 'industrial relations', the International Labour Office has always dealt with either the relationships between the State and the employers' and workers' organisation or the relations between the occupational organisation themselves. The I.L.O. thus uses the expression to denote such matters. as freedom of association and the protection of the right to organise, the application of the principles of the right to organise and the right of collective bargaining, collective agreements, conciliation and arbitration, and machinery for co-operation between the authorities and the occupational organisations at various levels of the economy.
Keywords: Industrial relations - India